Step towards the Development and New Prospects of Uzbek Higher Education - Umarov Abdurakhim Vakhitovich (Newinera Publisher, 2020)
In Uzbekistan, as well as in all areas, the study of international experience in higher education and the implementation of innovations have become one of the most pressing issues of the day. The article examines implementation of trends of modern foreign education practices in Uzbekistan education system. In traditional learning, teachers often allow students to dominate the group or depend on the group. In traditional learning, social skills are often not taught directly. Monitoring through observation and intervention is often carried out by the teacher when group learning is taking place.